Kajian Majaz Isti’arah dalam Lirik Qashidah ‘Yahabib Ya Habibi’ - Fitriyah, Nurul; Nurmala, Mia; Sopian, Asep (Kalamuna: Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2025)
The qasidah "Yahabib Ya Habibi" is widely celebrated in Indonesia, especially during Maulid and other religious events featuring sholawat. Its lyrics are renowned for their captivating use of Arabic rhetorical devices, rich in spiritual meaning. Previous research by Saepul Iman (2019) highlighted various forms of tashbih in the qasidah Burdah, emphasizing its linguistic depth. This study focuses on analyzing the Majaz Isti’arah (metaphors) in the lyrics of "Yahabib Ya Habibi" and how these metaphors convey religious messages in daily life.Using a descriptive qualitative method with content analysis, this research identifies verses containing Majaz Isti’arah based on the principles of Ilm al-Bayan (science of eloquence). The analysis involves determining the metaphor, its literal meaning, and its figurative (connotative) interpretation. The findings reveal that isti’arah tashrihiyyah frequently appears, featuring explicit comparisons where the source element (musta’ar minhu) is mentioned, while the target element (musta’ar lah) is implied. These metaphors enhance the emotional and spiritual depth of the lyrics, highlighting the qasidah’s role in conveying profound religious messages. This study underscores the linguistic and spiritual richness of qasidah as a cherished element of Islamic tradition.